1991
DOI: 10.1002/ca.980040304
|View full text |Cite
|
Sign up to set email alerts
|

Sagittal diameters of the lumbar spinal canal in normal adult Saudis

Abstract: The lumbar spinal canal may become narrowed as a result of a congenital defect (developmental stenosis) or following other changes associated with the vertebral column or its related structures (acquired stenosis). Stenosis of the canal may predispose the roots of the cauda equina to pressure or entrapment and consequently cause low back pain. Evidence suggests that the sagittal diameter is probably more frequently involved in stenotic lesions. Measurement of diameters from plain radiographs have been shown to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 13 publications
4
13
1
Order By: Relevance
“…The lower value was found in L3. The same remark was made by Amonoo-Kuofi et al [5] in Nigeria, by Tarek Aly et al [6] in Egypt, and by Lee et al [7] in Corea. The high APD in L1 and L2 could be explained by the bulge of the conus medullaris at this level.…”
Section: Lumbar Canal (Apd1) Dural Sac (Apd2)supporting
confidence: 67%
See 2 more Smart Citations
“…The lower value was found in L3. The same remark was made by Amonoo-Kuofi et al [5] in Nigeria, by Tarek Aly et al [6] in Egypt, and by Lee et al [7] in Corea. The high APD in L1 and L2 could be explained by the bulge of the conus medullaris at this level.…”
Section: Lumbar Canal (Apd1) Dural Sac (Apd2)supporting
confidence: 67%
“…The same remark was made by El-Rakhawy et al [8] in Pakistan. The comparison of the dimensions of our study with those of Amonoo-Kuofi et al [5] in Nigeria, of Ongolo Zogo et al [9] in Cameroon, of Tarek et al [6] in Egypt, and of El Rakhawy et al [8] in Pakistan and with that of Getroa [10] in Belgium did not find significant difference statistically. But our study found significant difference statistically in APD1 measurements with the study of Lee et al [7] in Korea.…”
Section: Lumbar Canal (Apd1) Dural Sac (Apd2)contrasting
confidence: 39%
See 1 more Smart Citation
“…Paired t test was used for analysis of side differences. The comparison of the measurements of the intervertebral foramen with previous reports [1,6,13,31,37,46] as well as their correlation with various osseous spinal landmarks will be addressed elsewhere.…”
Section: Methodsmentioning
confidence: 94%
“…Since the teardrop-like shape of the superior and inferior soft tissue parts of the foramen space are different from its osseous outline, clinical or cadaver measurements [7,25,40,52] [20,39] do not include intervertebral foramen diameters. Hitherto, the assessment of the macerated intervertebral foramen was surprisingly done for just one or two of the three main spinal regions [1,6,10,13] and explored in one prehistoric sample (950-1300 A.D.) only [10].…”
Section: Abstract Low Back Pain Originsmentioning
confidence: 99%